2008
DOI: 10.1182/blood-2008-05-156331
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of VEGF-A and VEGF-C target genes in lymphatic endothelium reveals endothelial-specific molecule-1 as a novel mediator of lymphangiogenesis

Abstract: Lymphatic vessel growth and activation, mediated by vascular endothelial growth factor (VEGF)–C and/or VEGF-A, have important roles in metastasis and in chronic inflammation. We aimed to comprehensively identify downstream molecular targets induced by VEGF-A or VEGF-C in lymphatic endothelium by analyzing the time-series transcriptional profile of treated human dermal lymphatic endothelial cells (LECs). We identified a number of genes, many not previously known to be involved in lymphangiogenesis, that were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 71 publications
5
132
0
4
Order By: Relevance
“…VEGF-C deals with growth of blood vessels and lymphatics (26). VEGF-A and C binds with a high affi nity to two related receptor tyrosine kinases expressed on vascular endothelial cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-C deals with growth of blood vessels and lymphatics (26). VEGF-A and C binds with a high affi nity to two related receptor tyrosine kinases expressed on vascular endothelial cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Endocan is a secreted proteoglycan (12) that is upregulated by growth factors and chemokines in vitro (13,14) and on tumor vasculature in several types of cancer (15)(16)(17), with diverse suggested biologic roles (18). Using quantitative reverse-transcription PCR (qRT-PCR) and immunohistochemistry, we found that endocan was strongly upregulated on tumor vascular endothelium and that its expression correlated with the invasiveness of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we next investigated whether HMGCR was expressed in LECs in our recently published LEC microarray data. We found that HMGCR is expressed in human dermal microvascular LECs that were used for this study (13) and also in murine intestinal LECs (14). Mevalonate, the product of HMGCR, and its derivatives farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP) build the basis for cholesterol synthesis.…”
Section: Identification Of Lymphangiogenic Sprouting Inhibitors By Lomentioning
confidence: 99%